2022
DOI: 10.3390/healthcare10101942
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Research about COVID-19 Vaccine Documented through Bibliometric and Visualization Analysis

Abstract: Due to COVID-19, people’s lives have changed greatly. In accordance with former experience, an efficacious vaccine is the most effective way to curb the pandemic; thus, many researchers have published related publications in the short term. Hence, this study aims at using bibliometric analysis and visualization to document research trends regarding COVID-19 vaccines, and offer some directions and suggestions for future research. Initially, all eligible publications were downloaded from Web of Science on 1 Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The Science Citation Index Expanded (SCIE) of the Web of Science Core Collection (WoSCC) database was chosen as the data source. It is the most frequently used and acceptable database for researchers in a variety of fields ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Science Citation Index Expanded (SCIE) of the Web of Science Core Collection (WoSCC) database was chosen as the data source. It is the most frequently used and acceptable database for researchers in a variety of fields ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bibliometric analysis offered an intuitive and effective foundation for integrating information, reflected interconnections between them, and predicted the development of cutting-edge advances in the area based on publications in this field ( 17 , 18 ). Recently, bibliometric analysis was widely adopted by scholars in neurology ( 19 ), vaccination ( 20 ), and otorhinolaryngology ( 21 ) related to COVID-19, especially the bibliometric analysis based on VOSviewer and CiteSpace software ( 22 , 23 ). However, bibliometric analysis of innate immunity in COVID-19 remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A few bibliometric studies have been published on assessment of global COVID-19 vaccines literature, which make the quantitative and qualitative assessment by way of analyzing various features of research output and citations. [7][8][9][23][24][25][26][27][28][29][30] With the rapid growth COVID-19 vaccines literature, it was difficult to go through such large number of publications appearing in various databases. It is observed that there has been a non-availability of any bibliometric study on HCPs papers on COVID-19 vaccine and any not study providing a quick, comprehensive synthesis of relevant information on the related scientific orientations, gaps, collaborations, themes, or dynamisms on COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%